2015
DOI: 10.1016/j.jjcc.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid annular motion velocity as a differentiation index of hypertrophic cardiomyopathy from hypertensive heart disease

Abstract: TAM-e' is a potentially useful index to differentiate HCM from HHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Some previous investigations have shown a sharp decrease in LV diastolic function in healthy women after 50–60 years of age, compared with men, suggesting that menopause might accelerate. [ 37 38 ] Moreover, postmenopausal state might be the independent and important risk factor for LVDD, although the LVDD of postmenopausal hypertensive women was affected by metabolic disorders. [ 39 ] Several animal studies have suggested that estrogen loss by ovariectomy-induced cardiomyocyte hypertrophy and cardiac fibrosis were important processes that contributed to LVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous investigations have shown a sharp decrease in LV diastolic function in healthy women after 50–60 years of age, compared with men, suggesting that menopause might accelerate. [ 37 38 ] Moreover, postmenopausal state might be the independent and important risk factor for LVDD, although the LVDD of postmenopausal hypertensive women was affected by metabolic disorders. [ 39 ] Several animal studies have suggested that estrogen loss by ovariectomy-induced cardiomyocyte hypertrophy and cardiac fibrosis were important processes that contributed to LVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on differentiating HCM from HHD have mainly focused on family history, genetic testing, or multimodality imaging exams. 5,[7][8][9][10][11] In terms of the imaging method, instead of LVMI, conventional morphologic parameters, such as LVMWT and regional bulging in the interventricular septum, have appeared to be relatively sensitive in differentiating the two disorders. 30 However, Jonathan et al demonstrated that an asymmetric hypertensive phenotype could overlap with the HCM MLVWT in approximately one in five hypertensive subjects, 31 which complicates differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies aimed at differentiating the etiologies of hypertrophy have been carried out one after another. 5,[8][9][10][11] The different manifestations of late gadolinium enhancement (LGE) presenting in the hypertrophic myocardium in the two diseases have recently been recognized. 12 LGE tends to be more prevalent in HCM, but it is lesser in extent and density in HHD.…”
mentioning
confidence: 99%
“…However, HCM can coexist with hypertension, leading to difficulty in differentiating it from hypertensive heart disease 21 , 23 . Compared to HCVD, patients with HCM are associated with a thicker right ventricular wall, greater ST-T changes, lower LV mass and fibrosis, and decreased tricuspid annular motion velocity early diastolic velocity (TAM-e′) 21 , 22 . The patients with comorbid HCM and hypertension tend to be older, and have higher risks of diabetes, coronary artery disease, and non-cardiac death 23 .…”
Section: Introductionmentioning
confidence: 99%